DEFAULTNESS PATTERNS: A DIACHRONIC ACCOUNT - Alshboul, Sabri; Al Shaboul, Yousef (Acta Neophilologica, 2010)
Most approaches to inflectional morphology propose a synchronic account for the establishment of defaultness in the plural inflection. The current research aims at exploring the representation of the default system in JA at a diachronic level. The grammar of JA displays two default plural forms: the sound feminine plural marked with the suffix -aat (e.g. mataar/matar-aat ‘an airport/airports’) where a suffixation rule predicts the occurrence of the default plural. The second default plural is the iambic broken plural marked with an internal vowel change (short – long vowel) (kursi/karaasi ‘a seat/seats’). Our diachronic analysis would take into account the default shift that occurred in the grammar of JA in two different periods: the Turkish period and the British period. The findings reveal the importance of the diachronic factors in determining the status of ‘defaultness’ in terms of the ability of the lexicon to accept two default inflections. So, JA consists a hierarchy that contains two defaults: the iambic broken plural and the sound feminine plural. This mechanism of accepting two defaults gives insights into applying this multiple default format crosslinguistically in which a grammar of a language can host a multiple default system.